The Comprehensive Systematic Review of Neuroprotection with Hypothermia in Traumatic Brain Injury - Ayub Quisa; Zakiul Ifkar Hamsi; Frederich Gabriel Xaverius Butar butar; Herfandi Dimas Anugrah (The Indonesian Journal of General Medicine, 2026)
Introduction: Traumatic brain injury (TBI) remains a leading cause of death and disability worldwide. Therapeutic hypothermia has been proposed as a neuroprotective strategy for decades, yet clinical trials have yielded conflicting results. Methods: This systematic review comprehensively analyzed 80 studies including randomized controlled trials, etc examining hypothermia for neuroprotection in TBI patients. Outcomes included functional neurological status (Glasgow Outcome Scale), mortality, intracranial pressure, biomarkers, and safety events. Results: Four major high-quality multicenter RCTs (POLAR n=511, Eurotherm3235 n=387, Hutchison et al. n=225, NABIS:H II n=232) demonstrated no benefit with hypothermia. POLAR showed no difference in favorable outcome (48.8% vs 49.1%; RR 0.99; P=0.94). Eurotherm3235 demonstrated harm (adjusted OR 1.53; P=0.04). However, significant positive signals emerged in specific subgroups: young patients (≤50 years) with evacuated mass lesions (77.8% favorable vs 33.3%; P=0.015) (15); acute subdural hematoma patients (75.0% vs 36.4%; P=0.045) (16); patients with initial ICP ≥30 mmHg (60.82% vs 42.71%; OR 1.861; P=0.039) (17); metabolic-targeted hypothermia (mortality 15.91% vs 34.09%; P=0.049) (25); pre-hospital initiation (65.1% vs 37.2%; P<0.05) (37); direct brain cooling (63.2% vs 15.4% good outcome; P=0.007) (55); and elderly patients (mortality 13.89% vs 30.56%; P=0.047) (13). Biomarker studies consistently demonstrated reduced NSE, S-100B, and oxidative stress markers with hypothermia (1-3,78). Discussion: The fundamental contradiction between large negative trials and numerous smaller positive Chinese single-center studies reflects critical differences in patient selection, injury subtypes, and cooling protocols. Diffuse injury may be harmed while focal evacuated lesions benefit. Conclusion: Prophylactic hypothermia for unselected severe TBI is not recommended. However, significant positive evidence supports hypothermia in young patients with evacuated mass lesions, acute SDH, refractory ICP ≥30 mmHg, and with metabolic-targeted or direct brain cooling approaches.